2021
DOI: 10.3389/fphar.2021.621856
|View full text |Cite
|
Sign up to set email alerts
|

Different Doses of Fingolimod in Relapsing-Remitting Multiple Sclerosis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The efficacy and safety of fingolimod for relapsing-remitting multiple sclerosis (RRMS) had been well verified in several large randomized controlled trials (RCTs) during the past decade. However, there are fewer systematic comparisons of different doses of fingolimod and whether the dose of 0.5 mg/d is the optimal one still remains to be solved.Objective: The objective of this systematic review was to evaluate the efficacy and safety of the four existing doses of fingolimod in the treatment of RRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Our stratified analyses demonstrated that S1PRMs did not have dose-dependent effects. One meta-analysis ( 46 ) published in 2021 that evaluated the efficacy and safety of different doses of fingolimod by examining 11 RCTs found that fingolimod 0.5 mg/d showed a significantly higher risk for overall AEs (RR, 1.25; 95% CI, 1.01–1.54), but no significant difference was found between the 0.5 mg/d fingolimod group and the control treatment group in serious AEs including bradycardia (RR, 2.97; 95% CI, 0.75–11.72) and atrioventricular block (RR, 2.03; 95% CI, 0.45–9.25). In our study, regardless of AE severity, fingolimod 0.5 mg/d and 1.25 mg/d were associated with a significant high risk for bradyarrhythmia consisting of bradycardia and atrioventricular block without a statistically significant difference (P interaction = 0.360).…”
Section: Discussionmentioning
confidence: 99%
“…Our stratified analyses demonstrated that S1PRMs did not have dose-dependent effects. One meta-analysis ( 46 ) published in 2021 that evaluated the efficacy and safety of different doses of fingolimod by examining 11 RCTs found that fingolimod 0.5 mg/d showed a significantly higher risk for overall AEs (RR, 1.25; 95% CI, 1.01–1.54), but no significant difference was found between the 0.5 mg/d fingolimod group and the control treatment group in serious AEs including bradycardia (RR, 2.97; 95% CI, 0.75–11.72) and atrioventricular block (RR, 2.03; 95% CI, 0.45–9.25). In our study, regardless of AE severity, fingolimod 0.5 mg/d and 1.25 mg/d were associated with a significant high risk for bradyarrhythmia consisting of bradycardia and atrioventricular block without a statistically significant difference (P interaction = 0.360).…”
Section: Discussionmentioning
confidence: 99%
“…The DNMC included the costs of traveling to other cities and accommodation as well as the meals consumed by the patient and his/ her family, and the nursing home care expenses determined by asking the patients. The human capital approach was used for IC calculation [ 48 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Administration of FTY720 at 1.25 mg/day in healthy adults–above which has proved unbeneficial for people with MS [ 7 ]–results in a maximum blood concentration (C max ) of 10.2 (±2.7) ng/mL at steady-state [ 9 ]; this concentration is 25000 times lower than its MIC 99 for C . albicans .…”
Section: Discussionmentioning
confidence: 99%
“…While being associated with beneficial outcomes and reasonable tolerability among people with immune-mediated conditions such as MS [ 5 , 6 ], safety and toxicity studies have shown both dose-dependent and time-dependent adverse effects associated with FTY720 [ 7 ]. The time-dependent adverse effects have been opportunistic infections, reactivation of latent viruses, malignancies, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation